2014
DOI: 10.1007/s10295-013-1362-7
|View full text |Cite
|
Sign up to set email alerts
|

Habitat-specific type I polyketide synthases in soils and street sediments

Abstract: Actinomycetes produce many pharmaceutically useful compounds through type I polyketide biosynthetic pathways. Soil has traditionally been an important source for these actinomycete-derived pharmaceuticals. As the rate of antibiotic discovery has decreased and the incidence of antibiotic resistance has increased, researchers have looked for alternatives to soil for bioprospecting. Street sediment, where actinomycetes make up a larger fraction of the bacterial population than in soil, is one such alternative env… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
11
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 11 publications
(11 citation statements)
references
References 37 publications
0
11
0
Order By: Relevance
“…Phylogenic analysis of type I PKS catalytic domains has shown that substrate specificity or reactivity of the domains often has a primary sequence determinant. For example, the acyltransferase (AT) domains cluster into malonyl‐CoA‐ and methylmalonyl‐CoA‐specific clades 36. β‐ketosynthase (KS) domains from trans AT pathways cluster based on the substitution at the α and β carbons of the upstream polyketide intermediates 7.…”
Section: Methodsmentioning
confidence: 99%
“…Phylogenic analysis of type I PKS catalytic domains has shown that substrate specificity or reactivity of the domains often has a primary sequence determinant. For example, the acyltransferase (AT) domains cluster into malonyl‐CoA‐ and methylmalonyl‐CoA‐specific clades 36. β‐ketosynthase (KS) domains from trans AT pathways cluster based on the substitution at the α and β carbons of the upstream polyketide intermediates 7.…”
Section: Methodsmentioning
confidence: 99%
“…While recognizing that more mundane environments can contain novelty for the bioprospector (e.g. forest soil [73], street sediments [74]) we opine that the case for prioritizing extreme biomes is sound as it moves bioprospecting action away from well-probed terrestrial streptomycetes towards microbial communities that have evolved under harsh selective conditions during the course of which novel biochemistry has been generated [75]. As Rateb et al report [66], a total of 46 natural products representing diverse chemical classes have been isolated from Atacama Desert actinobacteria during the past 7 years.…”
Section: Is Focus On the Extremobiosphere Justified?mentioning
confidence: 99%
“…This database was disproportionately actinomycetal possibly biasing the analysis. However this result was confirmed when the sequences were reanalyzed with a broader range of non-actinomycetal PKS domains [ 104 ].…”
Section: Unresolved Issues In Microbial Ecology That Limit Bioprosmentioning
confidence: 92%
“…In our work we compared PKSI amplicons of KS and AT from street sediments [ 104 ], which are enriched with Actinomycetes, and soils [ 46 ]. Many soil amplicons clustered with myxobacterial sequences.…”
Section: Unresolved Issues In Microbial Ecology That Limit Bioprosmentioning
confidence: 99%